Andrade, Nathanael J. (2018). The Journey of Christianity to India in Late Antiquity. Networks and the Movement of Culture - Ferrara, Marianna (ARYS. Antigüedad: Religiones y Sociedades, 2020)
ANDRADE, NATHANAEL J. (2018). The Journey of Christianity to India in Late Antiquity. Networks and the Movement of Culture. Cambridge: Cambridge University Press. 312 pp., 64,46€ [ISBN  978-1-1082-9695-3] [Book review]